VALIDITAS DAN RELIABILITAS INSTRUMEN ALAT UKUR SIT UP BERBASIS TEKNOLOGI DIGITAL - muhamad sazeli rifki; Fiky Farma (Jurnal Sporta Saintika, 2020)
This study aims to create a sit-up measurement tool based on digital technology that can provide the effectiveness and efficiency of testors and testees. firstly validated by an electrical expert and a test and measurement expert. Continue the small group test of 10 people and a large group of 20 people. Based on the results of the study showed that the Digital Technology-based Sit Up Test Measure was categorized as "Good / Eligible" as a sit-up test. The results were obtained from the validation of the 88.8% good / proper electro expert and the 94% good test and measurement expert / feasible. Thus the conclusion that the Digital Technology-based Sit Up Test Measurement Tool has been declared feasible to be used for future tests and measurements both testee and testor. Keywords: sit up test measurement tool